Faktor-Faktor yang mempengaruhi kualitas Pelaporan Keuangan pada Perusahaan Manufaktur yang Go Public di Indonesia - Hidayat, Widi; Elisabet, Elisabet (Lembaga Penerbitan Unversitas Esa Unggul, 2010)
This research aim to study and obtains empiric evidence to independent variable influence con-sisted of by corporate governance proxy to become ownership of institution, ownership of mana-gement and composition of board of commissioners, auditor independency, company growth, company age and leverage to quality of financial reporting of manufacturing business which go public in Indonesia. Besides also studies and obtains empiric evidence to operating cycle and com-pany size as control variable to quality of financial reporting of manufacturing business which go public in Indonesia. This research applies sample 67 companies with overall of sample 333 cases in range of time five years that is from the year 2002 up to the year 2006. This research measures quality of financial reporting based on estimation cash flow from operation applies Ordinary Least Squares. After found residual value each company every year his then is searched absolute of its value. When value absolute smaller than residual value absolute of industrial median (|ei,t=1|< Industry Median |ei,t=1|) hence variable quality of financial reporting will be given assessed by 1 and if other hence will be given value 0. After that, measurement of independent variables influence to variable quality of financial reporting is done to applies binary logistic regression. Fac-tors influencing quality of financial reporting to indicate that ownership of institution, ownership of management and composition of board of commissioners of all showing influence that is is not sig-nificant to quality of company financial reporting of hence inferential that corporate governance doesn't have an effect on significant to quality of company financial reporting. Company growth, le-verage and company size also has influence that is is not significant to quality of company financial reporting. While auditor independency, company age and operation cycle of company has influence signifikan to quality of company financial reporting. And together all the regressors have significant on quality of company financial reporting.Â Keywords: Financial Reporting Quality, Corporate Governance, Auditor Independency